2000
DOI: 10.1071/as00185
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Collaborative Learning Groups in Large Enrollment Introductory Astronomy

Abstract: Large-lecture introductory astronomy courses for undergraduate, non-science majors present numerous problems for faculty. As part of a systematic effort to improve the course learning environment, a series of small-group, collaborative learning activities were implemented in an otherwise conventional lecture astronomy survey course. These activities were used once each week during the regularly scheduled lecture period. After eight weeks, ten focus group interviews were conducted to qualitatively assess the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Second in the process level, a leader may resolve process related issues by alternating between synchronous and asynchronous activities of the members and thus better pace the discussion [50]. Third in the group development, a leader can also facilitate the group formation by ensuring evenly distributed participation [51] and cultivating mutual understanding among the members. And lastly, group dynamics become more positive through leaders' effort to support and encourage effective and positive group behaviors [9,10].…”
Section: Leadershipmentioning
confidence: 99%
“…Second in the process level, a leader may resolve process related issues by alternating between synchronous and asynchronous activities of the members and thus better pace the discussion [50]. Third in the group development, a leader can also facilitate the group formation by ensuring evenly distributed participation [51] and cultivating mutual understanding among the members. And lastly, group dynamics become more positive through leaders' effort to support and encourage effective and positive group behaviors [9,10].…”
Section: Leadershipmentioning
confidence: 99%
“…Continuing the original study over several additional semesters, Adams and Slater carefully examined the workings of collaborative groups in this setting. They probed the extent to which these groups help students learn (Skala, Slater, & Adams 2000). An exploration of group dynamics and behaviors showed that female students interact differently in all-female groups as compared to mixed groups .…”
Section: "So Happy Together" (Studies On Collaborative Learning In Asmentioning
confidence: 99%
“…Some of the instruments discussed in section 6.1, as well as some instruments designed and used only at a particular location and have been used to assess students taught traditionally and students taught by new or redesigned curricula, courses or methods. This research [208][209][210][211][212][213][214][215][216] and the research discussed in indicate that students taught by courses, curricula and methods that incorporate the results of research in physics learning, have a better conceptual understanding of physics and that their ability to solve quantitative problems is at least as good as students taught traditionally. This assessment is ongoing and is being continually evaluated [217][218][219][220][221][222][223].…”
Section: Assessment Of Students Taught By New and Traditional Instruc...mentioning
confidence: 99%